Review. Issue 2 (1st October 2019) - Broadhead, Samantha
Provoking the Field: International Perspectives on Visual Arts PhDs in Education, Anita Sinner, Rita Irwin and Jeff Adams (eds) (2019) Bristol: Intellect Ltd, 276 pp., ISBN 978-1-78320-991-0, p/bk, £25